Rethinking sexual crimes: from women’s consent to men’s responsibility - Herring, J (Faculdade de Direito, Universidade de Lisboa, 2023)
This article proposes a rethinking of the law’s approach to rape. It is claimed that the focus of the law should be on the responsibility of the defendant to ensure they have sufficiently good reasons to engage in sex. At the moment the law of rape, particularly as it plays out in rape trials, focuses on the state of mind of the victim. The academic debates centre on whether consent is to be assessed subjectively or objectively; whether the victim needs to positively demonstrate opposition to the sexual act or whether it is sufficient if the victim does not positively manifest consent; and when apparent consent might be negated through threats or deception. At trial, the case often turns on whether or not the victim is believed when she says she did not consent. However fascinating these arguments are, it will be argued, they are somewhat beside the point. The key question is whether the defendant had sufficient reason to perform the act.